Magnesium Regulates Endothelial Barrier Functions through TRPM7, MagT1, and S1P1 - Zhu, Donghui (Adv Sci (Weinh), 2019)
Mg(2+)‐deficiency is linked to hypertension, Alzheimer's disease, stroke, migraine headaches, cardiovascular diseases, and diabetes, etc., but its exact role in these pathophysiological conditions remains elusive. Mg(2+) can regulate vascular functions, yet the mechanistic insight remains ill‐defined. Data show that extracellular Mg(2+) enters endothelium mainly through the TRPM7 channel and MagT1 transporter. Mg(2+) can act as an antagonist to reduce Ca(2+) signaling in endothelium. Mg(2+) also reduces the intracellular reactive oxygen species (ROS) level and inflammation. In addition, Mg(2+)‐signaling increases endothelial survival and growth, adhesion, and migration. Endothelial barrier integrity is significantly enhanced with Mg(2+)‐treatment through S1P1‐Rac1 pathways and barrier‐stabilizing mediators including cAMP, FGF1/2, and eNOS. Mg(2+) also promotes cytoskeletal reorganization and junction proteins to tighten up the barrier. Moreover, Mg(2+)‐deficiency enhances endothelial barrier permeability in mice, and Mg(2+)‐treatment rescues histamine‐induced transient vessel hyper‐permeability in vivo. In summary, Mg(2+)‐deficiency can cause deleterious effects in endothelium integrity, and Mg(2+)‐treatment may be effective in the prevention or treatment of vascular dysfunction.